THE INTEGRATION OF QUANTUM COMPUTING AND DIGITAL FORENSICS: OPPORTUNITIES AND CHALLENGES - Muzmmil Memon; Muhammad Ahsan Naeem; Farheen Memon (Spectrum of Engineering Sciences, 2025)
Purpose: It analyzes the impact of new findings in quantum computing on forensic techniques, as it is urgent to check the reliability of current tools in light of potential quantum threats. Driven by the discovery that quantum attack algorithms may expose the current forensic system to attack, the research examines how quantum algorithms and modern AI are transforming forensics. It draws on current cryptographic and forensic foundations, shows they cannot handle a post-quantum world and outlines a new structure that adds quantum-safe methods and effective forensics. This research used 14 validated models and followed a thematic approach built on Theory, including Post-Quantum Cryptography (PQC), Quantum Key Distribution (QKD), ForensicLLM and Digital Forensics as a Service (DFaaS). Using literature and conceptual mapping, we investigated how these theories influence forensic readiness, the way tasks are managed and tool automated processing. The research has found that present forensic systems do not meet the demands of possible quantum decryption and that using AI-assisted, transformer-based tools in forensics can greatly improve activity and analysis accuracy. In addition, the research finds that organizational readiness plays a major role as a moderating factor. The findings from this research will guide plans for modernization and may be examined using future studies in different countries and institutions.